Attention effects on the processing of task-relevant and task-irrelevant speech sounds and letters - Mittag, Maria; Inauri, Karina; Huovilainen, Tatu; Leminen, Miika; Salo, Emma; Rinne, Teemu; Kujala, Teija; Alho, Kimmo (Frontiers in Neuroscience, 2013)
We used event-related brain potentials (ERPs) to study effects of selective attention on the processing of attended and unattended spoken syllables and letters. Participants were presented with syllables randomly occurring in the left or right ear and spoken by different voices and with a concurrent foveal stream of consonant letters written in darker or lighter fonts. During auditory phonological and non-phonological tasks, they responded to syllables in a designated ear starting with a vowel and spoken by female voices, respectively. These syllables occurred infrequently among standard syllables starting with a consonant and spoken by male voices. During visual phonological and non-phonological tasks, they responded to consonant letters with names starting with a vowel and to letters written in dark fonts, respectively. These letters occurred infrequently among standard letters with names starting with a consonant and written in light fonts. To examine genuine effects of attention and task on ERPs not overlapped by ERPs associated with target processing or deviance detection, these effects were studied only in ERPs to auditory and visual standards. During selective listening to syllables in a designated ear, ERPs to the attended syllables were negatively displaced during both phonological and non-phonological auditory tasks. Selective attention to letters elicited an early negative displacement and a subsequent positive displacement of ERPs to attended letters being larger during the visual phonological than non-phonological task suggesting a higher demand for attention during the visual phonological task. Active suppression of unattended speech during the auditory phonological and non-phonological tasks and during the visual phonological tasks was suggested by a rejection positivity to unattended syllables. We also found evidence for suppression of the processing of task-irrelevant visual stimuli in visual ERPs during auditory tasks involving left-ear syllables.